(untitled) (Advancements in Homeopathic Research, 2022)
Dermatitis is most common skin problem all over the world. In the word “dermatitis,” “derm” means “skin” and “itis” means “inflammation.” Dermatitis literally means inflammation of the skin. It is a specific type of allergic cutaneous manifestation of antigen antibody reaction. Dermatitis causes no serious harm to your body. It is not a contagious disease. Homeopathy is very useful in cases of dermatitis so we should know its clinical presentation and representation of the disease in different clinical repertories.